PENERAPAN WEBSITE DESA SEBAGAI MEDIA INFORMASI PENGENALAN POTENSI DESA SUMBEREJA - Salwa Ibnatisna Sya'bana; Yunike Berry; Rusham Rusham (Universitas Islam 45 Bekasi, 2023)
The progress of information technology is closely linked to the digital and informatics fields. It has become an integral part of people's lives, from using mobile phones to accessing the internet with its various features and functions. The impact of information technology is not limited to urban areas, as it has also reached rural areas. For instance, Sumbereja village still uses manual methods to gather information. This situation inspired the author to create a website for Sumbereja village, which would enable the wider community to gain a better understanding of the village through the web. To address this issue, the Real Work Lecture Activities of Islamic University 45 Bekasi proposed a work program. The program aimed to create an